2019
DOI: 10.1177/0954406219897089
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis modeling of piezoelectric actuators with the frequency-dependent behavior using a hybrid model

Abstract: In order to overcome the problem of positioning inaccuracy caused by nonlinear hysteresis of piezoelectric actuators, a hybrid model based on least-squares support vector machine and Bouc–Wen model is proposed to model the rate-dependent hysteresis of piezoelectric actuators. A rate-independent Bouc–Wen model and its parameters identification method is established as the basis of least-squares Bouc–Wen model. Least-squares support vector machine, which is optimized by particle swarm optimization, is introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Wei et al (2014) employed the extended LSA manner-recursive LSA that is a variation of LSA and dynamically estimates unknown system parameters, and a limited memory approach to complete accurate online identification for asymmetrical BW model parameters. Fujii et al (2018) utilized a recursive LSA to identify a discrete classical BW model of a bimorph-type PA. Qian et al (2020) regulated the classical BW model parameters of a PA at various frequencies by least-squares support vector machine accurately.…”
Section: System Modelingmentioning
confidence: 99%
“…Wei et al (2014) employed the extended LSA manner-recursive LSA that is a variation of LSA and dynamically estimates unknown system parameters, and a limited memory approach to complete accurate online identification for asymmetrical BW model parameters. Fujii et al (2018) utilized a recursive LSA to identify a discrete classical BW model of a bimorph-type PA. Qian et al (2020) regulated the classical BW model parameters of a PA at various frequencies by least-squares support vector machine accurately.…”
Section: System Modelingmentioning
confidence: 99%
“…Some studies have tried to develop different parameter identification methods. In addition to the classical least squares algorithm, 17 meta-optimization such as particle swarm algorithm (PSO), 18 genetic algorithm 19 and fish swarm algorithm (AF) 20 are applied to the parameter identification of the model. And some studies have verified that Antlion algorithm (ALO) is robust and simple.…”
Section: Introductionmentioning
confidence: 99%
“…Nematollahi et al 15 suggested a wavelet-based neural network for inverse identification of piezoelectric beam. Qian et al 16 introduced a hybrid least-squares support vector machine and Bouc-Wen model to model the ratedependent hysteresis of piezoelectric actuators. Zhang et al 17 investigated an optimal hysteresis model of PZT actuator using particle swarm optimization-based neural network.…”
Section: Introductionmentioning
confidence: 99%